2004
DOI: 10.1016/j.molbrainres.2004.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine coregulates multiple pathways involved in protein modification/degradation in rat brain

Abstract: Previously, we used cDNA microarrays to demonstrate that the phosphatidylinositol and MAP kinase signaling pathways are regulated by nicotine in different rat brain regions. In the present report, we show that, after exposure to nicotine for 14 days, ubiquitin, ubiquitinconjugating enzymes, 20S and 19S proteasomal subunits, and chaperonin-containing TCP-1 protein (CCT) complex members are upregulated in rat prefrontal cortex (PFC) while being downregulated in the medial basal hypothalamus (MBH). In particular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 60 publications
4
34
0
2
Order By: Relevance
“…Dunckley and Lukas found that nicotine exposure alters the expression of contactin 1, UBE2C, UBE2S, and Perkin in SH-SY5Y cells Lukas 2003, 2006) with a heavy emphasis on the ubiquitin proteosomal degradation pathway. Kane et al (2004) also reported changes in the proteosomaldegradation pathway using microarray analysis of nicotinetreated rat brain, but the contributing receptor subtypes in this study are not clear.…”
Section: Discussionmentioning
confidence: 73%
“…Dunckley and Lukas found that nicotine exposure alters the expression of contactin 1, UBE2C, UBE2S, and Perkin in SH-SY5Y cells Lukas 2003, 2006) with a heavy emphasis on the ubiquitin proteosomal degradation pathway. Kane et al (2004) also reported changes in the proteosomaldegradation pathway using microarray analysis of nicotinetreated rat brain, but the contributing receptor subtypes in this study are not clear.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, altered protein kinetics has been proposed as one method of altering nicotinic receptor function as observed in recent nicotinic response work in cultured neurons (35). Evidence for a conserved role of mammalian cct8 in the nicotine response (36) includes strong expression in mouse neural tissue (37). In addition, rat cct8 mRNA is upregulated in the prefrontal cortex after exposure to nicotine (38).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral assays have been developed in a number of animal models to measure many of the known physiological manifestations associated with drug addiction, including locomotor sensitization (Benwell & Balfour, 1992;Kalivas & Stewart, 1991), conditioned place preference (CPP; Tzschentke, 1998), self-administration (Stairs, Neugebauer, & Bardo, 2010), and withdrawal (André, Gulick, Portugal, & Gould, 2008). Behavioral assays define changes induced by drug exposure and enable differential molecular analysis of the resulting transcriptional (i.e., gene expression) and epigenetic states (Kane, Konu, Ma, & Li, 2004;Kumar et al, 2005;Levine et al, 2005;Nestler, 2008;Renthal et al, 2007;Romieu et al, 2008;Shen et al, 2008). As the reinforcing properties of addictive drugs are highly conserved, behavioral assays have been adapted to zebrafish to study addiction to cocaine (Darland & Dowling, 2001), ethanol (Lockwood, Bjerke, Kobayashi, & Guo, 2004;Peng et al, 2009), amphetamines (Ninkovic & Bally-Cuif, 2006;Webb et al, 2009), and opiates (Bretaud et al, 2007;Lau, Bretaud, Huang, Lin, & Guo, 2006;Sanchez-Simon & Rodriguez, 2008).…”
Section: Drug Addiction and Dependencementioning
confidence: 99%